Pembelajaran Karakter dengan Tamanisasi Demokratis di Lingkungan Taman Kanak-Kanak - Budi, Eka Setya (THUFULA, 2017)
This research aims to know learning character process by using tamanisasi demokratis in kindergarten and the changes of the students’ character after being taught by tamanisasi demokratis. This research design uses cross-sectional and longitudinal design. While the steps in this research are: planning, action, observation and reflection. This research result proves that there is change of the students after beng treated by learning character process using tamanisasi demokratis. The change can be seen from every aspects which are used in observing the students. Each aspect used in observing the students of kinderganten increases to 75% in average. From the result, it can be concluded that tamanisasi demokrasi in kindergartens can change the students’ characters.